Effects of Learning by Analogy on Senior High School Students’ Achievement in Genetics in Ilorin, Nigeria - Sulaiman, Musa Mohammed; Bello, Ganiyu; Ahmed, Mulkah Adebisi (Jurnal Pendidikan Progresif, 2022)
Genetics has been identified in literature as one of the hard-to-learn biological concepts despite its importance to human existence. Therefore, there is the need for students to have deep conceptual understanding of the concept. The effectiveness of analogy on proper understanding of scientific concepts abound in literature, hence, this study examined the effects of analogy instructional strategy on senior school student s’ achievement in genetics. The study was quasi-experimental with a sample of 112 students purposively selected from two intact classes. Data gathered were analysed using ANCOVA. Findings from the study revealed that a significant difference existed in the achievement of students taught genetics with analogy and those taught using the conventional teaching approach in favour of the analogy group (F(1, 109) = 20.88, p<0.05). It was therefore, recommended that biology teachers should adopt the use of analogy instructional strategy in teaching genetics and other difficult concepts in biology. Key Words: analogy, score level, senior school students’, achievement, genetics.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202211